Effective Approaches to Preventing Burnout in Educators - Nurgaliyeva, S.A. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2025)
This study investigates the prevalence and impact of emotional burnout among teachers, focusing on its three primary dimensions: emotional exhaustion, depersonalization, and reduced personal accomplishment. The research employs a mixed-method approach, utilizing observation, surveys, individual and group interviews, and quasi-experimental designs. The results indicate that a significant proportion of teachers experience moderate emotional exhaustion (50.7 %) and moderate depersonalization (39.5 %), with a smaller yet concerning group showing high levels of emotional exhaustion (13.5 %) and high depersonalization (9.5 %). The study also explores the relationship between locus of control and burnout, revealing that teachers with an internal locus of control (62.5 %) exhibit lower levels of burnout and higher motivation, while those with an external locus of control (37.5 %) report higher burnout and lower motivation. The findings emphasize the need for targeted interventions, such as improving time management, stress-relief strategies, and fostering an internal locus of control through professional development programs. This research highlights the critical role of supporting teacher well-being to prevent burnout and ensure the long-term effectiveness and job satisfaction of educators. The study calls for school administrators and policymakers to prioritize teacher mental health through structured support systems, professional growth opportunities, and promoting a culture of collaboration within educational institutions.
Мұғалімдердің күйзеліске ұшырауының алдын алудың тиімді тәсілдері
Эффективные подходы к профилактике выгорания у педагогов
Keywords: teacher well-being; emotional exhaustion; depersonalization; personal accomplishment; teacher motivation; professional development